Thioether and related ligand complexes of copper : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science - Palmer, Kevin Charles (Massey University, 1975)
The dithioethers 2,5-dithiahexane (DTH) and 3,6-dithiaoctane (DTO) form the following stable copper (II) complexes; Cu(S͡S)X₂ where S͡S=DTH or DTO and X=Cl or Br, and also Cu(DTH)₂(BF₄)₂ The complexes Cu(DTO)₂(BF₄)₂ and Cu(DTO)(NO₃)₂.H₂O decomposed over a short period of time. The following copper (I) complexes were also prepared: [CuX)₂DTO]n where X=Cl or Br, Cu(DTO)I, Cu(DTH)Cl, [Cu(DTH)X]n where X=Br or I, [Cu(DTO)SCN]n and Cu(DTO)₂ BF₄. The complexes were characterised using infra-red spectroscopy, visible-U.V. spectroscopy, Raman spectroscopy, x-ray powder photography, conductivity and molecular weight measurements, and proton nuclear magnetic resonance spectroscopy. Some reactions were also carried out by displacement of the dithioethers with a variety of monodentate and bidentate ligands, e.g. pyridine, ethylenediamine, trimethylphosphine sulphide, sodium dimethyldithiophosphinate dihydrate, and triphenylphosphine which also forms an adduct with Cu(DTH) Cl to give Cu(DTH) (Ø₃P) Cl.
Keywords: Copper; Coordination compounds; Ligands